2021
DOI: 10.1055/s-0041-1734009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Multiple Sclerosis Awareness and Knowledge among the Community of Jeddah, Saudi Arabia

Abstract: Objective Multiple sclerosis (MS) is a degenerative disease of the central nervous system that can lead to lifelong disabilities. There is a significant increase in the global incidence of the disease. In Saudi Arabia (SA), the western region has the greatest number of MS cases. However, there is a lack of studies and research to assess public knowledge in the region. Thus, we aim to assess the public's knowledge of MS in Jeddah, SA. Methodology We conducted a cross-sectional study surveying 468 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
1
0
0
Order By: Relevance
“…We also found that the age group 18-24 years had the least level of awareness compared to the age group 25-44 years. This is in contradistinction with other reports [3,4] which demonstrated no significant variation in knowledge about MS between gender and age groups. This be explained by the fact that the age group 25-44 years is the one most affected by MS, and they are more exposed to MS patients than younger participants, thus increasing their knowledge about the disease.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We also found that the age group 18-24 years had the least level of awareness compared to the age group 25-44 years. This is in contradistinction with other reports [3,4] which demonstrated no significant variation in knowledge about MS between gender and age groups. This be explained by the fact that the age group 25-44 years is the one most affected by MS, and they are more exposed to MS patients than younger participants, thus increasing their knowledge about the disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding demographic characteristics, most of the participants (366 out of 507 or 72.1%) were females and 27.9% were males, which is in accordance with the study from Jeddah [4].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A majority (72%) fell within the 18-22 age group, with 28% in the 23-27 age group. While both age groups demonstrated improvement, the 23-27 age group exhibited more excellent knowledge, aligning with findings in a study by Farran et al [15], which highlighted significant differences in knowledge between males and females regarding MS.…”
Section: Discussionsupporting
confidence: 89%